Implementation of Corruption Prevention in Health High Schools Makassar South Sulawesi - Suat, Hatty; Rieuwpassa, Sarmalina; Haulussy, Rais Rahman; Suat, Rahmawati; Borut, Mohamad; Anurogo, Dito; Verawati, Verawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
One of the efforts we must make to eradicate corruption is to increase the anti-corruption movement. Efforts to eradicate corruption cannot rely solely on enforcement efforts that fall under the authority of law enforcement institutions. Efforts to prevent corruption by participating in building an anti-corruption culture in society are an important factor in efforts to eradicate corruption. As an element of society, students are expected to act as agents of change and driving forces for the anti-corruption movement in society. To be able to play an active role, students need to be equipped with sufficient knowledge about the ins and outs of corruption and its eradication. Anti-corruption education is intended so that students can clearly understand the problems of corruption that are occurring and efforts to prevent them. This article explains anti-corruption education and also to find out how anti-corruption education is taught on campus. Efforts to equip students can be achieved in various ways, including: outreach activities, campaigns, seminars or lectures. Anti-corruption education for students aims to provide sufficient knowledge about the ins and outs of corruption and its eradication as well as instilling anti-corruption values. The long-term goal is to foster an anti-corruption culture among students and encourage students to play an active role in efforts to eradicate corruption in Indonesia.